Educação financeira e a produção de vídeos curtos: uma proposta para a abordagem temática com alunos 3º ano do ensino médio - Prado, Paola do (2025)
This Master’s dissertation, structured within the research line in Educational Practices in Science and Mathematics Teaching, investigates Financial Education through the production of short videos by High School students. The study aims to address the topic from the students' social and family context, interconnecting theory and practice, demonstrating the applicability of related concepts to real-life situations. The research considers the guidelines of the Brazilian National Common Curricular Base (BNCC), which considers Financial Education as a cross cutting theme of Brazilian Basic Education and includes it within the High School education itineraries for in-depth study. This is qualitative study, grounded in Paulo Freire’s pedagogical principles – particularly his concepts of reading the world, dialogue, student autonomy and freedom – fundamental assumptions that structure this work, since the entire process of producing short videos is based on the students reality and the issues brought by them. The central research question guiding this study is: What are the implications of High School students production of short videos for understanding Financial Education concepts and applying them to their realities? To address this question, the study general objective is to analyze the educational implications of producing short videos with high school students to study Financial Education concepts relevant to their contexts. A didactic sequence was developed following the Didactic Engineering research methodology and applied to two third year high school classes, at a public school in Marau/RS, Brazil. The didactic sequence seeks to promote classroom discussions on Financial Education concepts arising from the students' family context, aiming to highlight the subject’s relevance and explore possibilities for changing their realities, therefore, all video productions were developed based on this premise. Taking it into account, the sequence of activities was divided into three stages: theme delimitation, video production and a festival in which the videos produced for other classes at the school were presented. Thus, this dissertation resulted, as an educational product, in the guide entitled “Financial Education and Short Videos: Guidance Guide for High School Teachers”, available on the platform Educapes http://educapes.capes.gov.br/handle/capes/1000317, which will serve as a basis for educators interested in implementing this proposal in their classroom. Data collection and analysis involved the use of the researcher-teacher’s class diary, a collaborative virtual mural created by participating students, and evaluation questionnaires completed by the students regarding their experiences. The development of these activities allowed students to construct knowledge collaboratively, exchanging ideas and experiences among themselves, as well as increasing interaction among themselves. By providing students with the opportunity to study Financial Education concepts based on their realities, they were able to broaden their concepts and become aware of previously unknown subjects and contexts. In addition, the production of videos gave students the freedom to create and the autonomy to use their own experiences in these audiovisual materials, as well as increasing student involvement and participation by presenting a different dynamic from what they are used to practicing in the classroom. Thus, at the end of the activity, students recognized the significance of studying Financial Education for structuring a balanced life and making informed, critical decisions concerning financial matters.